(untitled) (Community Based Medical Journal, 2022)
A cross-sectional, descriptive study was done at a rural high school in Zakiganj Upazila of Sylhet District, Bangladesh, between January and December of 2014, to determine knowledge and practice of oral health and hygiene and oral health status among school going adolescents. Students from three classes: class VIII, IX and X, and aged 12-16 years were taken for the study. Study samples were collected by using simple random sampling technique. A total of 90 students were divided into two age groups: 12-14 years and 15-16 years. A pre-designed, self-administered questionnaire was used for demographic survey and knowledge of oral health and hygiene (a 10-point questionnaire) and practice (a 7-point questionnaire). Then a plane mouth mirror and periodontal probe was used for examining oral health status in those school children. Oral hygiene status was measured by simplified Green and Vermillion Oral Hygiene Index. The mean age of the respondents was 14.37±0.50 years. Females were 68 (75.6%) and males were 22 (24.4%). 31 (34.4%) were from class VIII, 30 (33.3%) from class IX and 29 (32.2%) were from class X. 33.3% of the respondents have scored below the mean of the total knowledge score while 66.7% has scored above the mean (6.86±2.05). Pearson’s correlation coefficient (+0.342) revealed that an increase in knowledge score would lead to increase in practice score. The younger group had higher mean knowledge score than older group (7.15+1.35 vs. 6.58+2.54; P=0.017); however, no significant difference was found between males and females (6.90±1.74 vs. 6.85±2.15; P=0.432). There was no significant difference in Debris Index (DI), Calculous Index (CI) and Oral Health Index (OHI) scores in between age groups and genders. On educational status, significant difference was observed only in OHI score (P=0.001) among those three classes of students. Overall, only 31% had good oral hygiene, while 59% respondents had fair and 10% had poor oral hygiene status. CBMJ 2021 January: vol. 10 no. 01 P: 30-36